2008
DOI: 10.1007/s00248-008-9468-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Tracking of Motile Algae Assisted by Algal Cell’s Vorticity Field

Abstract: Previously published experimental work by other authors has shown that certain motile marine bacteria are able to track free-swimming algae by executing a zigzag path and steering toward the algae at each turn. Here, we propose that the apparent steering behaviour could be a hydrodynamic effect, whereby an algal cell's vorticity and strain-rate fields rotate a pursuing bacterial cell in the appropriate direction. Using simplified models for the bacterial and algal cells, we numerically compute the trajectory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…2B, Inset and Table S1). This result is in line with predictions from recent theoretical models for E. coli and V. alginolyticus (18,20) and, to the best of our knowledge, represents the first experimental quantification of the dependence of the chemotactic velocity on the swimming speed. The steady-state chemotactic velocities ranged from V C = 0.2-3.5 μm/s (Fig.…”
Section: Strong Chemotaxis At High Swimming Speeds Results From Reducedsupporting
confidence: 91%
“…2B, Inset and Table S1). This result is in line with predictions from recent theoretical models for E. coli and V. alginolyticus (18,20) and, to the best of our knowledge, represents the first experimental quantification of the dependence of the chemotactic velocity on the swimming speed. The steady-state chemotactic velocities ranged from V C = 0.2-3.5 μm/s (Fig.…”
Section: Strong Chemotaxis At High Swimming Speeds Results From Reducedsupporting
confidence: 91%
“…Yet our results suggest that the diversity in a population should be extremely weak in the integral of the response γ and stronger in the memory λ and the running time τ r . Indeed, variations in the rotational diffusivity D of individual bacteria are expected at the level of both thermal (6) and mechanical (39) contributions. It is known that the diversity of τ r is appreciable; it will be of interest to gather experimental data on the correlations among variations in τ r and those in D and λ.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for sinking marine snow particles and fecal pellets (93) but potentially also for swimming phytoplankton cells (19,108). The release of solutes, coupled with the movement relative to the water, distorts the otherwise nearly spherical diffusion boundary layer into a cometlike plume ( Fig.…”
Section: Ephemeral Nutrient Pulsesmentioning
confidence: 99%
“…Consequently, these experimental observations indicate that the chemosensory capabilities of marine bacteria may exceed what previous theory had predicted. However, while this impressive "chasing" ability was initially attributed to chemotaxis alone, one subsequent theoretical study has suggested that the origin of the phenomenon might be purely hydrodynamic, whereby the fluid velocity gradients in the wake of the swimming alga reorient bacteria so that they remain in the wake (108). While this remains an interesting possibility, the very sharp turns executed by the chasing bacteria still suggest an active behavior, leaving this topic open for further investigation.…”
Section: Chemotaxis Toward Phytoplanktonmentioning
confidence: 99%